A perovskite solar cell modified with PCN-224 quantum dots and its preparation method

By introducing PCN-224 QDs into perovskite solar cells and doping them into Spiro-OMeTAD solution, the problem of poor stability of perovskite solar cells in humid environments is solved, and high-efficiency energy conversion and good moisture resistance are achieved.

CN115000312BActive Publication Date: 2025-04-01HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210653383.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-09
Publication Date
2025-04-01
Estimated Expiration
2042-06-09

AI Technical Summary

Technical Problem

Perovskite solar cells have poor stability in humid environments and are difficult to prepare on a large scale, which affects their energy conversion efficiency and commercial application.

Method used

By introducing PCN-224 QDs into the light-absorbing layer and hole transport layer of perovskite solar cells, using its large specific surface area and abundant N and O active sites, Lewis acid-base coordination with Pb2+ in the perovskite film, increasing the perovskite grain size and reducing the defect state density. At the same time, PCN-224 QDs are doped into the Spiro-OMeTAD precursor solution to prepare a hole transport layer, limiting the migration of Li+, reducing hole formation and water vapor infiltration.

Benefits of technology

The energy conversion efficiency of perovskite solar cells has been significantly improved, reaching 22.51%, and the performance stability is reduced by only 9% in high humidity environments, significantly improving the battery's moisture resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003686785400000011
    Figure HDA0003686785400000011
  • Figure HDA0003686785400000012
    Figure HDA0003686785400000012
  • Figure HDA0003686785400000021
    Figure HDA0003686785400000021
Patent Text Reader

Abstract

The present invention discloses a preparation method of a perovskite solar cell modified with PCN-224QDs, including the preparation of a substrate, an electron transport layer, a perovskite light absorption layer modified with PCN-224QDs, a hole transport layer modified with PCN-224QDs and a gold electrode, wherein PCN-224QDs are obtained by freeze drying and are doped in a perovskite antisolvent and a hole transport layer, respectively, to prepare an efficient and stable perovskite solar cell. The N and O atoms of PCN-224QDs can act as a Lewis base and react with the Lewis acid Pb in the perovskite film. 2+ Lewis acid-base coordination is performed, which significantly increases the size of the perovskite grains and reduces the defect state density. PCN‑224QDs are doped into the Spiro‑OMeTAD precursor solution to prepare the hole transport layer. Due to the ordered spatial structure of PCN‑224QDs and the N and O active sites in its structure, they can jointly limit the Li + The migration of the hole transport layer is reduced, and its agglomeration effect is reduced, thereby avoiding the formation of holes in the hole transport layer, slowing down the penetration of water vapor, and significantly improving the energy conversion efficiency and moisture resistance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy solar cell materials, and in particular to a perovskite solar cell modified based on PCN-224 QDs and a preparation method thereof. Background Art

[0002] Perovskite solar cells have attracted widespread attention due to their simple manufacturing process and low manufacturing cost. And due to their excellent photoelectric properties, such as long carrier lifetime, high absorption coefficient, high mobility, and adjustable band gap, they have attracted great attention from scholars from all over the world. From 3.8% photoelectric conversion efficiency in 2009 to 25.5% today, its efficiency has been rapidly improved. However, although perovskite solar cells have developed very rapidly in a short period of time, their easy decomposition of the light-absorbing layer, poor device stability, and difficulty in large-scale preparation have seriously hindered their further development and large-scale commercialization.

[0003] In order to improve the moisture stability of the device, some researchers have used black phosphorus quantum dots or flakes to modify the interior and interface of the battery to improve its performance. For example, black phosphorus nanosheets are used between the perovskite light absorption layer and the hole transport layer. Although the P element in black phosphorus can passivate the uncoordinated Pb in the perovskite, 2+ , improving the hole extraction ability and achieving certain results in stability. However, due to the super moisture absorption performance of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI), it is easy to form holes in the hole transport layer due to the agglomeration effect, which accelerates the infiltration of water vapor, degrades black phosphorus, forms phosphoric acid, and accelerates the erosion of the perovskite light-absorbing layer, which has a serious impact on the performance of the entire battery. In addition, black phosphorus is expensive and difficult to use on a large scale.

[0004] Therefore, it is necessary to develop a perovskite solar cell and its preparation method that can not only improve the energy conversion efficiency but also enhance its moisture resistance. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing perovskite solar cells modified with PCN-224 QDs on one hand, which solves the above-mentioned technical problems.

[0006] A method for preparing a perovskite solar cell modified with PCN-224 QDs, comprising the following steps: (1) using transparent FTO conductive glass as a substrate, (2) preparing an electron transport layer, wherein the electron transport layer comprises a titanium dioxide dense electron transport layer and a titanium dioxide mesoporous electron transport layer, (3) preparing a perovskite light absorbing layer modified with PCN-224 QDs, (4) preparing a hole transport layer modified with PCN-224 QDs, and (5) preparing a gold electrode; the substrate, the electron transport layer, the light absorbing layer and the hole transport layer are sequentially connected by spin coating;

[0007] Wherein: the preparation steps of step (3) are as follows:

[0008] a. Dissolve 100 mg TCPP, 300 mg ZrOCl2·8H2O, and 2.8 g BA in 100 mL DMF, stir at 90 °C for 4-5 h, centrifuge the obtained PCN-224 nano-MOFs at 18,000 rpm for 30 min, and wash with DMF twice more;

[0009] b. Then, the collected PCN-224 nano-MOFs were placed in a vacuum oven to obtain PCN-224 nano-MOFs powder. 100 mg of PCN-224 nano-MOFs were dissolved in 100 mL of ultrapure water at room temperature and then treated with a cell-disrupting ultrasonic instrument with a power of 200 W for 5-6 h to obtain a suspension containing PCN-224 QDs.

[0010] c. Finally, the PCN-224 QDs in the supernatant were collected by centrifugation at 12000 rpm for 20 min, dialyzed and washed with ultrapure water, and then freeze-dried for later use;

[0011] d. The perovskite precursor solution is dripped onto the electron transport layer by anti-solvent titration method and high-speed spin coating is performed. During the spin coating process, the reserved chlorobenzene anti-solvent solution containing 6-10 mg / mL PCN-224 QDs is titrated. The anti-solvent titration time is counted down to 10-15 seconds, and then the perovskite light absorbing layer is obtained by heating and annealing.

[0012] The preparation steps of step (4) are as follows: spin-coat a hole transport layer precursor solution containing 2-6 mg / mL PCN-224 QDs onto the surface of the perovskite light absorbing layer to obtain a PCN-224 QDs modified hole transport layer.

[0013] Furthermore, in the step (2), the titanium dioxide precursor solution is spin-coated onto the transparent FTO conductive glass, and then heated to 500°C and sintered to obtain a dense electron transport layer; then the titanium dioxide slurry diluted with anhydrous ethanol is spin-coated onto the dense electron transport layer, and the temperature is gradually increased until 500°C and sintered to obtain a mesoporous electron transport layer with a thickness of 400 nm.

[0014] Furthermore, the step-by-step temperature increase treatment is as follows: the temperature is increased to 130°C within 20 minutes, and the treatment is carried out at this temperature for 10 minutes; the temperature is increased to 325°C within 20 minutes, and the treatment is carried out at this temperature for 10 minutes; the temperature is increased to 375°C within 5 minutes, and the treatment is carried out at this temperature for 10 minutes; the temperature is increased to 450°C within 10 minutes, and the treatment is carried out at this temperature for 10 minutes; the temperature is increased to 500°C within 5 minutes, and sintered at this temperature for 30 minutes.

[0015] Furthermore, in the step (3), 1.105 mmol FAI, 1.16 mmol PbI2, 0.195 mmol MABr, 0.195 mmol PbBr2 and 0.068 mmol MABr are dissolved in 1 mL of a mixed solution of DMF and DMSO in a volume ratio of 4:1, and stirred for 60 minutes to obtain a perovskite precursor solution.

[0016] Furthermore, according to the method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 1, it is characterized in that in the step (3), the perovskite precursor solution is dripped into the electron transport layer by first coating it by a spin coating process at 1000 rpm for 10 s, and then coating it by a spin coating process at 4000 rpm for 30 s.

[0017] Furthermore, in the step (3), the annealing temperature is 100-120°C, and the annealing time is 60-80 min.

[0018] Furthermore, in the step (4), the spin coating rate of the hole transport layer precursor solution of PCN-224 QDs is 4000 rpm, and the spin coating time is 15-30 s.

[0019] Furthermore, in the step (5), a gold electrode is prepared on the surface of the hole transport layer by a vacuum evaporation process, and the thickness of the gold electrode is 80-100 nm.

[0020] On the other hand, a PCN-224 QDs-modified perovskite solar cell prepared according to the above method is provided, wherein the perovskite solar cell consists of a substrate, an electron transport layer, a modified perovskite light absorbing layer, a doped hole transport layer and a gold electrode.

[0021] The PCN-224 QDs are introduced into the perovskite light absorption layer and the hole transport layer by using the method for modifying the perovskite solar cell based on PCN-224 QDs provided by the present invention. The PCN-224 QDs have the characteristics of large specific surface area and rich N and O active sites. The N and O atoms can act as Lewis bases and react with the Lewis acid Pb in the perovskite film. 2+ Lewis acid-base coordination was performed, which significantly increased the perovskite grain size and reduced the defect state density. PCN-224 QDs were further doped into the Spiro-OMeTAD precursor solution to prepare a hole transport layer. Due to the ordered spatial structure of PCN-224 QDs and the N active sites in its structure, they can jointly limit the Li +The migration of the hole transport layer is reduced, and its agglomeration effect is reduced, thereby avoiding the formation of holes in the hole transport layer, slowing down the penetration of water vapor, and significantly improving the energy conversion efficiency of the battery by up to 22.51%, and the moisture resistance is only reduced by 9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the structure of a perovskite solar cell.

[0023] Figure 2 The JV curves of the perovskite solar cells are shown in Figure 1, where the A curve represents the perovskite solar cell in comparative example 1 without the addition of PCN-224 QDs for modification; the B curve represents the perovskite solar cell in comparative example 2 with the addition of PCN-224 QDs to modify only the perovskite light-absorbing layer; and the C curve represents the perovskite solar cell in embodiment 1 with the addition of PCN-224 QDs for modification.

[0024] Figure 3 This is a performance stability test of perovskite solar cells at a humidity of (50±20RH%), wherein curve A represents the perovskite solar cell in comparative example 1 without the addition of PCN-224 QDs for modification; curve B represents the perovskite solar cell in comparative example 2 in which PCN-224 QDs are added and only the perovskite light-absorbing layer is modified; curve C represents the perovskite solar cell in example 1 in which PCN-224 QDs are added for modification. DETAILED DESCRIPTION

[0025] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0026] Embodiment 1: A method for a perovskite solar cell modified with porphyrin zirconium-based organic metal framework quantum dots (PCN-224 QDS), comprising the following steps:

[0027] (1) Transparent FTO conductive glass as substrate

[0028] Pre-treat FTO conductive glass with a size of 2cm×2cm, a thickness of 2mm, and a square resistance of 7Ω. Place FTO in the mold in order, and then clean it step by step with detergent, deionized water, ethanol, acetone, and isopropanol under ultrasonic conditions for 20 minutes. After the ultrasonic treatment, dry it with N2, and finally treat it with UV ozone for 15 minutes.

[0029] (2) Preparation of electron transport layer

[0030] Preparation of titanium dioxide dense electron transport layer:

[0031] First, 350 μL of tetraisopropyl titanate was quickly added to 2.5 mL of anhydrous ethanol and stirred continuously for 5 min to obtain a tetraisopropyl titanate solution; 35 μL of 2M HCl solution was added to 2.5 mL of anhydrous ethanol and stirred continuously for 5 min to obtain an HCl solution; the HCl solution was quickly dripped into the tetraisopropyl titanate solution and stirred continuously for 30 min to obtain a titanium dioxide precursor solution. Next, 80 μL of the titanium dioxide precursor solution was applied to the FTO conductive glass and coated with a spin coating process at 2000 rpm for 60 s. Finally, the film was heat treated, wherein the sintering process was: heated to 500 °C at a heating rate of 5 °C / min and sintered at this temperature for 30 min.

[0032] Preparation of titanium dioxide mesoporous electron transport layer:

[0033] First, the purchased TiO2 slurry was diluted with anhydrous ethanol, where the mass ratio of TiO2 slurry to anhydrous ethanol was 1:6. After dilution, the slurry was magnetically stirred for 24 hours before use. Then, 80 μL of the above slurry was applied to the dense electron transport layer and the film was coated by spin coating at 4000 rpm for 60 seconds. Finally, the film was heat-treated to obtain a mesoporous transport layer with a thickness of 400 nm. The heat treatment sintering process was as follows: the temperature was raised to 130°C within 20 minutes and treated at this temperature for 10 minutes; the temperature was raised to 325°C within 20 minutes and treated at this temperature for 10 minutes; the temperature was raised to 375°C within 5 minutes and treated at this temperature for 10 minutes; the temperature was raised to 450°C within 10 minutes and treated at this temperature for 10 minutes; the temperature was raised to 500°C within 5 minutes and sintered at this temperature for 30 minutes.

[0034] (3) Preparation of PCN-224 QDs modified perovskite light absorbing layer:

[0035] a. Dissolve 100 mg TCPP (tris 2-chloropropyl phosphate), 300 mg ZrOCl2·8H2O, and 2.8 g BA (benzoic acid) in 100 mL DMF (N,N-dimethylformamide), stir at 90 °C for 4-5 h, centrifuge the obtained PCN-224 nano-MOFs at 18000 rpm for 30 min, and wash with DMF twice more;

[0036] b. Then, the collected PCN-224 nano-MOFs were placed in a vacuum oven overnight to obtain PCN-224 nano-MOFs powder. 100 mg of PCN-224 nano-MOFs were dissolved in 100 mL of ultrapure water at room temperature and then treated with a cell-disrupting ultrasonic instrument with a power of 200 W for 5-6 h to obtain a suspension containing PCN-224 QDs.

[0037] c. Finally, the PCN-224 QDs in the supernatant were collected by centrifugation at 12000 rpm for 20 min, dialyzed and washed with ultrapure water, and then freeze-dried for later use;

[0038] d. Using the anti-solvent titration method, a perovskite precursor solution is dripped onto the electron transport layer and high-speed spin-coated. During the spin-coating process, the prepared chlorobenzene (CB) anti-solvent solution containing PCN-224 QDs is titrated, and then heated and annealed to obtain a perovskite light-absorbing layer; wherein, the preparation of the perovskite precursor solution is:

[0039] The perovskite light-absorbing layer was prepared by a one-step anti-solvent method. The entire process was carried out in a glove box filled with nitrogen. 0.05 FA 0.81 MA 0.14 PbB 0.45 I 2.55 1.105mmol FAI, 1.16mmol PbI2, 0.195mmol MABr, 0.195mmol PbBr2 and 0.068mmol MABr were first dissolved in 1mL of a mixed solution (DMF and DMSO were mixed in a volume ratio of 4:1), and then stirred for 60min to form a perovskite precursor solution. 2) Then, 80μL of the perovskite precursor solution was applied to the dioxidized peptide mesoporous electron transport layer and coated by a two-step spin coating process, first at 1000rpm, 10s of spin coating process; then at 4000rpm, 30s of spin coating process, and at the same time, 200μL of 8mg / ml PCN-224QDs chlorobenzene (CB) solution was quickly dripped in at the countdown of 13s. Finally, the film was immediately placed on a heating table at 110℃ for 70min.

[0040] (4) Preparation of PCN-224 QDs modified hole transport layer:

[0041] First, 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solvent and ultrasonicated for 1 min to obtain a lithium bis(trifluoromethanesulfonyl)imide solution; then 72.3 mg of 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene, 17.5 μL of lithium bis(trifluoromethanesulfonyl)imide solution, and 28.8 μL of tributyl phosphate were added to 1 mL of chlorobenzene in sequence, and ultrasonicated for 1 min to completely dissolve them to obtain a Spiro-OMeTAD solution; PCN-224 QDs were dispersed in the Spiro-OMeTAD solution to obtain a Spiro-OMeTAD solution containing PCN-224 QDs at a concentration of 4 mg / ml. After the perovskite film was cooled, 80 μL of the prepared Spiro-OMeTAD solution was applied to its surface and coated by spin coating at 4000 rpm for 20 s; finally, it was placed in a drying cabinet overnight to fully oxidize it.

[0042] (5) Preparation of gold electrodes

[0043] The air compressor, circulating water, power supply, mechanical pump, inflation valve and sample chamber of the high vacuum resistance evaporation coating instrument are turned on in sequence; 0.3 g of gold wire is weighed into the tungsten evaporation boat in the sample chamber, and the sample is placed on the rotating fixed frame of the sample chamber, and the front stage valve and the molecular pump are opened in sequence to evacuate the vacuum, and when the vacuum degree drops below 10-4Pa, the evaporation power switch is turned on again, and the power is slowly increased to 70A first, and after preheating for 40s, the power is adjusted to 100A for evaporation, and the gold residue is observed from the observation room. When the gold is completely evaporated, the current is immediately slowly adjusted to zero, and then the molecular pump, the front stage valve and the mechanical pump are closed in sequence, and finally the vent valve is opened to take out the device, and a gold electrode is prepared on the surface of the hole transport layer, and the thickness of the gold electrode is 80-100nm.

[0044] The present invention also includes a perovskite solar cell with enhanced hole transport based on porphyrin zirconium-based organic metal framework quantum dots (PCN-224 QDs) prepared through the above steps, including a transparent FTO conductive glass substrate, an electron transport layer, a modified perovskite light absorbing layer, a doped hole transport layer and a gold electrode.

[0045] Example 2: The difference between Example 2 and Example 1 is that steps (3) and (4) are different, specifically: (3) Preparation of PCN-224QDS modified perovskite light absorbing layer

[0046] The perovskite light-absorbing layer was prepared by a one-step anti-solvent method. The entire process was carried out in a glove box filled with nitrogen. 0.05 FA 0.81 MA 0.14 PbB 0.45 I 2.551.105mmol FAI, 1.16mmol PbI2, 0.195mmol MABr, 0.195mmol PbBr2 and 0.068mmol MABr were first dissolved in 1mL of a mixed solution (DMF and DMSO were mixed in a volume ratio of 4:1), and then stirred for 60min to form a perovskite precursor solution; 2) Then, 80μL of the perovskite precursor solution was applied to the carbon dioxide mesoporous electron transport layer and coated by a two-step spin coating process, first at 1000rpm, 10s of spin coating process; then at 4000rpm, 30s of spin coating process, and at the same time, 200μL of 6mg / ml PCN-224QDs chlorobenzene (CB) solution was quickly dripped in the countdown of 10s. Finally, the film was immediately placed on a heating table at 100℃ for 60min.

[0047] (4) Preparation of PCN-224 QDs modified hole transport layer

[0048] First, 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solvent and ultrasonicated for 1 min, which was recorded as A. Then, 72.3 mg of 2,2',7,7'-tetra-(dimethoxydiphenylamine)-spirofluorene, 17.5 μL of A solution, and 28.8 μL of tributyl phosphate were added to 1 mL of chlorobenzene in sequence, and ultrasonicated for 1 min to completely dissolve them to obtain a Spiro-OMeTAD solution. PCN-224 QDs were dispersed in the Spiro-OMeTAD solution to obtain a Spiro-OMeTAD solution containing PCN-224 QDs at a concentration of 2 mg / ml. After the perovskite film was cooled, 80 μL of the prepared Spiro-OMeTAD solution was applied to its surface and coated by spin coating at 4000 rpm for 15 s. Finally, it was placed in a drying cabinet overnight to fully oxidize it.

[0049] Example 3: The difference between Example 3 and Example 1 is that steps (3) and (4) are different, specifically: (3) Preparation of PCN-224 QDS modified perovskite light absorbing layer

[0050] The perovskite light-absorbing layer was prepared by a one-step anti-solvent method. The entire process was carried out in a glove box filled with nitrogen. 0.05 FA 0.81 MA 0.14 PbB 0.45 I 2.551.105mmol FAI, 1.16mmol PbI2, 0.195mmol MABr, 0.195mmol PbBr2 and 0.068mmol MABr were first dissolved in 1mL of a mixed solution (DMF and DMSO were mixed in a volume ratio of 4:1), and then stirred for 60min to form a perovskite precursor solution; 2) Then, 80μL of the perovskite precursor solution was applied to the substrate and coated with a two-step spin coating process, first at 1000rpm, 10s of spin coating process; then at 4000rpm, 30s of spin coating process, and at the same time, 200μL of 10mg / ml PCN-224 QDs chlorobenzene solution was quickly dripped in the countdown of 15s. Finally, the film was immediately placed on a heating table at 120℃ for 80min of heat treatment.

[0051] (4) Preparation of PCN-224 QDs modified hole transport layer

[0052] First, 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solvent and ultrasonicated for 1 min, which was recorded as A. Then, 72.3 mg of 2,2',7,7'-tetra-(dimethoxydiphenylamine)-spirofluorene, 17.5 μL of A solution, and 28.8 μL of tributyl phosphate were added to 1 mL of chlorobenzene in sequence, and ultrasonicated for 1 min to completely dissolve them to obtain a Spiro-OMeTAD solution. PCN-224 QDs were dispersed in the Spiro-OMeTAD solution to obtain a Spiro-OMeTAD solution containing PCN-224 QDs at a concentration of 6 mg / ml. After the perovskite film was cooled, 80 μL of the prepared Spiro-OMeTAD solution was applied to its surface and coated by spin coating at 4000 rpm for 30 s. Finally, it was placed in a drying cabinet overnight to fully oxidize it.

[0053] Comparative Example 1: Perovskite solar cell with light absorption layer not modified by PCN-224 QDs

[0054] The difference between Comparative Example 1 and Example 1 is that: in step (3), the perovskite precursor solution is dripped onto the electron transport layer by anti-solvent titration method and high-speed spin coating is performed, and during the spin coating process, a chlorobenzene anti-solvent solution not containing PCN-224QDs is titrated, and then heating and annealing are performed to obtain the perovskite light absorbing layer, and the other steps are the same.

[0055] Comparative Example 2: Perovskite solar cell with hole transport layer not modified by PCN-224 QDs

[0056] The difference between Comparative Example 2 and Example 1 is that in step (4), a hole transport layer precursor solution without PCN-224 QDs is directly spin-coated onto the surface of the perovskite light absorption layer to obtain a PCN-224 QDs-modified hole transport layer. The other steps are the same.

[0057] The performance test results of the perovskite solar cells prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Tables 1 and Figure 2 , Figure 3 As shown in the figure, after the perovskite solar cell was modified with PCN-224 QDs, the energy conversion efficiency of the cell increased from 19.09% to 22.51%, an increase of 18%; then the performance stability test was carried out under high humidity (50±20RH%) environmental conditions. After 30 days, the energy conversion efficiency of the battery in comparative example 1 decreased by 55%, which was only 45% of the initial value; after 30 days, the energy conversion efficiency of the battery in comparative example 2 decreased by 21%, which was 79% of the initial value; and after the perovskite solar cell was modified with PCN-224 QDs, its energy conversion efficiency only decreased by 9%, and the performance was relatively stable.

[0058] Table 1 Performance comparison of perovskite solar cells of Example 1 and Comparative Example 1

[0059] project Energy conversion efficiency (%) Performance stability (%), i.e. energy efficiency decline index Embodiment 1 22.51% 9% Embodiment 2 21.92% 12% Embodiment 3 21.64% 15% Comparative Example 1 19.09% 55% Comparative Example 2 21.59% 21%

[0060] In summary, the preparation method of the perovskite solar cell modified with PCN-224 QDs of the present invention firstly obtains PCN-224 QDs by ultrasonic solvent method, and then drops the anti-solvent solution containing PCN-224 QDs in the spin coating process of the perovskite light absorbing layer, wherein the N and O atoms of the anti-solvent solution can act as Lewis base and react with the Lewis acid Pb in the perovskite film. 2+ Lewis acid-base coordination is performed, thereby significantly increasing the perovskite grain size and reducing the defect state density. Finally, PCN-224 QDs are doped into the Spiro-OMeTAD precursor solution to prepare a hole transport layer. The N and O active sites in its structure can jointly limit the migration of Li+ and reduce its agglomeration effect, thereby avoiding the formation of holes in the hole transport layer, slowing down the infiltration of water vapor, significantly improving the energy conversion efficiency and moisture resistance of the battery, and the charge extraction efficiency is as high as 22.51%. The method of the present invention has simple process and convenient operation, and provides a feasible solution for accelerating the industrialization of perovskite solar cells in the future.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a perovskite solar cell modified with PCN-224 QDs, characterized in that: The following steps are involved: (1) transparent FTO conductive glass as a substrate, (2) preparation of an electron transport layer, wherein the electron transport layer includes a titanium dioxide dense electron transport layer and a titanium dioxide mesoporous electron transport layer, (3) preparation of a PCN-224 QDs modified perovskite light absorbing layer, (4) preparation of a PCN-224 QDs modified hole transport layer, (5) preparation of a gold electrode; the substrate, the electron transport layer, the light absorbing layer and the hole transport layer are sequentially connected by spin coating; Wherein: the preparation steps of step (3) are as follows: a. Dissolve 100 mg TCPP, 300 mg ZrOCl2·8H2O, and 2.8 g BA in 100 mL DMF, stir at 90 °C for 4-5 h, centrifuge the obtained PCN-224 nano-MOFs at 18,000 rpm for 30 min, and wash with DMF twice more; b. Then, the collected PCN-224 nano-MOFs were placed in a vacuum oven to obtain PCN-224 nano-MOFs powder. 100 mg of PCN-224 nano-MOFs were dissolved in 100 mL of ultrapure water at room temperature and then treated with a cell-disrupting ultrasonic instrument with a power of 200 W for 5-6 h to obtain a suspension containing PCN-224 QDs. c. Finally, the PCN-224QDs in the supernatant were collected by centrifugation at 12000 rpm for 20 min, dialyzed and washed with ultrapure water, and then freeze-dried for later use; d. The perovskite precursor solution is dripped onto the electron transport layer by anti-solvent titration method and high-speed spin coating is performed. During the spin coating process, the reserved chlorobenzene anti-solvent solution containing 6-10 mg / mL PCN-224 QDs is titrated. The anti-solvent titration time is counted down to 10-15 seconds, and then the perovskite light absorbing layer is obtained by heating and annealing. The preparation steps of step (4) are as follows: spin-coat a hole transport layer precursor solution containing 2-6 mg / mL PCN-224 QDs onto the surface of the perovskite light absorbing layer to obtain a PCN-224 QDs modified hole transport layer.

2. The method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 1, characterized in that: In the step (2), a titanium dioxide precursor solution is spin-coated onto a transparent FTO conductive glass, and then heated to 500°C for high-temperature sintering to obtain a dense electron transport layer; then a titanium dioxide slurry diluted with anhydrous ethanol is spin-coated onto the dense electron transport layer, and the temperature is gradually increased until 500°C for high-temperature sintering to obtain a mesoporous electron transport layer with a thickness of 400 nm.

3. The method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 2, characterized in that: The step-by-step temperature increase treatment is as follows: raise the temperature to 130°C within 20 minutes and treat at this temperature for 10 minutes; raise the temperature to 325°C within 20 minutes and treat at this temperature for 10 minutes; raise the temperature to 375°C within 5 minutes and treat at this temperature for 10 minutes; raise the temperature to 450°C within 10 minutes and treat at this temperature for 10 minutes; raise the temperature to 500°C within 5 minutes and sinter at this temperature for 30 minutes.

4. The method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 1, characterized in that: In the step (3), 1.105 mmol FAI, 1.16 mmol PbI2, 0.195 mmol MABr, 0.195 mmol PbBr2 and 0.068 mmol MABr are dissolved in 1 mL of a mixed solution of DMF and DMSO in a volume ratio of 4:1, and stirred for 60 minutes to obtain a perovskite precursor solution.

5. The method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 1, characterized in that: In the step (3), the perovskite precursor solution is dripped into the electron transport layer by firstly coating the film by a spin coating process at 1000 rpm for 10 s, and then coating the film by a spin coating process at 4000 rpm for 30 s.

6. The method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 1, characterized in that: In the step (3), the annealing temperature is 100-120° C. and the annealing time is 60-80 min.

7. The method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 1, characterized in that: In the step (4), the spin coating rate of the hole transport layer precursor solution of PCN-224 QDs is 4000 rpm, and the spin coating time is 15-30 s.

8. The method for preparing a perovskite solar cell modified with PCN-224 QDs according to claim 1, characterized in that: In the step (5), a gold electrode is prepared on the surface of the hole transport layer by using a vacuum evaporation process, and the thickness of the gold electrode is 80-100 nm.

9. A PCN-224 QDs modified perovskite solar cell prepared according to the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Perovskite solar cell based on Fe<+3> doped black phosphorus quantum dot modification and method thereof

    CN110767814A

  • Perovskite solar cell and preparation method thereof

    CN112490367A